Evaluation of Castor (Ricinus communis L.) Genotypes and Their Feeding Values on Rearing Performance of Eri Silkworm (Samia cynthia ricini Boisduval) (Lepidoptera: Saturniidae) in Southwest Ethiopia. (3rd October 2022) - Tulu, Dereje; Aleme, Melkam; Mengistu, Gezahegn; Bogale, Ararsa; Shifa, Kedir; Mendesil, Esayas
Abstract : The quality of feed plays an important role in the growth and development of silkworms and eventually in the economic traits of cocoons. This study was conducted to evaluate ten castors ( Ricinus communis L.) genotypes and their feeding values on the rearing performance of Eri Silkworm ( Samia cynthia ricini Boisduval) (Lepidoptera: Saturniidae) at Tepi, southwest Ethiopia. A total of ten castor genotypes were evaluated in a randomized complete block design (RCBD), and the suitability of castor genotypes as feed for a mixed strain of Eri-silkworm was also evaluated in a completely randomized design (CRD) under laboratory conditions. A hundred worms were used in each replication. Castor genotypes showed significant differences in fresh leaf yield. Among the castor genotypes tested, genotype 219645 recorded 439 g of ten fresh leaf yields. Results of Eri-silkworm rearing performance depict that a shorter larval period (22 days), a higher effective rate of rearing (94.54%), and a shorter life cycle (58 days) were observed in Eri-silkworm fed on leaves of the 200390 genotype, while a higher larval weight (6.16 g) was recorded in the Abaro genotype. However, higher cocoon weight (3.26 g), pupal weight (2.46 g), shell weight (0.45 g), and silk ratio (13.80%) were found in Eri-silkworms fed on leaves of genotype 219645. Hence, based on silkworm rearing performance, genotype 219645 showed relatively superior results and is recommended for future development work. Further studies should continue giving more emphasis to the multilocation study of genotype 219645 to understand its performance in the diverse growing environment.